'Effectivites': an imperative legal principle in resolving the Senkaku / Diaoyu islands dispute - Ali Mohamed, Ashgar Ali; Ansari, Abdul Haseeb; Ahmad, Muhamad Hassan (The Indian Law Institute, 2018)
This paper analyses critically the judicial interpretation and application of the principle of 'effectivities' by the international courts and tribunals in resolving inter-state territorial and boundary dispute.